TUJUAN DAN MANFAAT PERJANJIAN PERKAWINAN - Faradz, Haedah (Jurnal Dinamika Hukum, 2008)
Societal perception which still consider dim towards Marriage Agreement makes Marriage Agreement seldom doing by layman. This case happens because Marriage Agreement considers does not ethic, and even does not fit with oriental custom. Actually Law No.1 Year 1974 concerning Marriage law has not yet  cleared to arrange Marriage Agreement, it only declares that both parties that is husband and wife, article 29 Law No.1 Year 1974 mentioned above can conclude that inscribed Agreement which mentioned is Marriage Agreement. In fact Marriage Agreement carries a nice purpose and profit, because it is a preventive action to simplify distribution of their property. Kata kunci: Perkawinan dan perjanjian